2021
DOI: 10.1002/cne.25157
|View full text |Cite
|
Sign up to set email alerts
|

Controlling for activity‐dependent genes and behavioral states is critical for determining brain relationships within and across species

Abstract: The genetic profile of vertebrate pallia has long driven debate on homology across distantly related clades. Based on an expression profile of the orphan nuclear receptor NR4A2 in mouse and chicken brains, Puelles et al. (The Journal of Comparative Neurology, 2016, 524, 665–703) concluded that the avian lateral mesopallium is homologous to the mammalian claustrum, and the medial mesopallium homologous to the insula cortex. They argued that their findings contradict conclusions by Jarvis et al. (The Journal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the hippocampus Nurr1 expression levels may affect long-term memory function (Peña de Ortiz et al, 2000 ; Colón-Cesario et al, 2006 ) and Alzheimer’s disease pathology ( Moon et al, 2015 , 2019 ). It has been suggested that Nurr1 expression may be influenced by behavioral and sensory stimuli ( Biegler et al, 2021 ). However, supporting evidence in the mammalian brain, particularly in the claustrum, remains scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampus Nurr1 expression levels may affect long-term memory function (Peña de Ortiz et al, 2000 ; Colón-Cesario et al, 2006 ) and Alzheimer’s disease pathology ( Moon et al, 2015 , 2019 ). It has been suggested that Nurr1 expression may be influenced by behavioral and sensory stimuli ( Biegler et al, 2021 ). However, supporting evidence in the mammalian brain, particularly in the claustrum, remains scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This was shortly before the Jarvis et al [2013] and Chen et al [2013] reports appeared (preliminary results were presented in that meeting). I later recorded detailed critical comments on some aspects I considered highly aberrant in these two papers [Puelles et al, 2017] and there are recent reactions on their side in Gedman et al [2021] and Biegler et al [2021] (see below).…”
Section: Sd Briscoe and Cw Ragsdalementioning
confidence: 99%
“…This supposedly only can occur thanks to evolutionarily conserved brain connections and related input, output, and associative functions. The hodologist that follows Faunes et al [2015] vein inexplicably pretends to find order in the assumed developmental and morphologic chaos, apparently because of his/her faith in the unique discriminative power of hodological similarity analysis in adults (see also in this respect the likewise aberrant thesis of Biegler et al [2021] that comparative functional analysis should also be an inexcusable requirement in embryonic studies). In my discrepant view, genomic structure, development, and morphologic structure are unavoidable preliminary constraints in comparative functional homology thought.…”
Section: Sd Briscoe and Cw Ragsdalementioning
confidence: 99%
“…Eggs were collected from coat-color validated zebra finch nests for incubation at 38 °C and 50–60% humidity. For in situ hybridization, we used previously collected brain tissue from adult zebra finch males (≥ 90 days old, n = 3) that were euthanized following an overnight period in a dark sound isolation chamber, as described previously 67 .…”
Section: Methodsmentioning
confidence: 99%
“…Digoxigenin- (DIG) conjugated probes for ZEB2 (Genbank: DV946921) and PVALB (Genbank: DQ215755) were generated and applied onto male zebra finch brain sections from previous studies, as detailed previously 67 . For the HTR1A DIG-labeled probe, the sequence was amplified from zebra finch cDNA using pri mers containing the T7 and T3 promoters (Supplementary Table 9), and the probe was generated and used in the same way as the others.…”
Section: Methodsmentioning
confidence: 99%